2014
DOI: 10.4314/sajas.v44i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolite concentrations and postpartum resumption of ovarian cyclicity in Sanga cows

Abstract: An experiment was conducted to investigate the effect of concentrations of certain blood nutrientsensitive metabolites and the resumption of postpartum ovarian cyclicity in 16 Sanga cows (mean BCS 5). Blood samples were taken from cows from weeks 1 to 13 (90 days) postpartum, processed and the plasma progesterone concentration measured to determine the resumption of postpartum ovarian cyclicity. The cows were classified as having resumed ovarian cyclicity when a plasma progesterone concentration of ≥1.0 ng/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
8
18
0
Order By: Relevance
“…The overall mean blood cholesterol level of 2.34 mmol/l recorded was similar to the value 2.47 mmol/l obtained by Damptey et al. () for Sanga cows grazing extensively on pasture in the Accra plains of Ghana. Elevated albumin concentrations were associated with early resumption of ovarian activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall mean blood cholesterol level of 2.34 mmol/l recorded was similar to the value 2.47 mmol/l obtained by Damptey et al. () for Sanga cows grazing extensively on pasture in the Accra plains of Ghana. Elevated albumin concentrations were associated with early resumption of ovarian activity.…”
Section: Discussionsupporting
confidence: 88%
“…Perhaps increased lipolysis in these two groups of cows due to their lower glucose concentrations resulted in increased plasma concentrations of low-density lipoproteins which is associated with increased rate of cholesterol synthesis, as reported in some studies (Ahmad et al 2004;Saleh et al 2011). The overall mean blood cholesterol level of 2.34 mmol/l recorded was similar to the value 2.47 mmol/l obtained by Damptey et al (2014) for Sanga cows grazing extensively on pasture in the Accra plains of Ghana. Elevated albumin concentrations were associated with early resumption of ovarian activity.…”
Section: Discussionsupporting
confidence: 84%
“…Mapiye et al (2012) were observed that most of the indigenous Nguni cattle in South Africa had urea concentration below the reference range which was possibly due to lower intakes of crude proteins on the rangeland pasture. In our study, animals had higher concentration of urea in the blood than in previous study, because cattle were kept mostly in stables with temporary access to the good pastures, as in Sanga cattle from Ghana (Damptey et al 2014) and Thai cattle (Boonprong et al 2007).…”
Section: Discussionmentioning
confidence: 45%
“…The welfare of goats under these grazing systems and floor types needs attention and their nutritional status needs evaluation. Nutritional adequacy to the goats can be evaluated using blood metabolites, daily weight gains, body condition scores (BCS) [ 3 ] and carcass characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Blood biochemistry gives a reliable and consolidated measure of the sufficiency of dietary nutrients that can be used regardless of the physiological state of the animal [ 6 ]. Metabolites that reflect an animal’s protein status include: albumin, globulin, total protein (TP), creatinine, and urea [ 3 ]. Albumin concentration decreases when an animal is exposed to deficiencies in dietary protein or parasitism [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%